PERSEPSI MAHASISWA UNIVERSITAS PGRI ADI BUANA SURABAYA TERHADAP TRADISI TATO MAHASISWA ASAL KEPULAUAN MENTAWAI - Nur Rohmah; Magfirotul Hamdiah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
This research is entitled Perceptions of Students of Universitas PGRI Adi Buana Surabaya on the Tattoo Tradition of Students from the Mentawai Islands. The research aims to determine the students' views about the Mentawai tattoo tradition which is against the world of education. The method used in this research is descriptive qualitative method. The results of the study showed that the perception of students at the PGRI Adi Buana University Surabaya towards tattoos was very positive, more than 75% of students already understood the outline of tattoos, both tattoos as a symbol of identity and as art. Most students agree that tattoos have now become a trend that cannot be separated from modern society. Even the pictures are so diverse and interesting that what was once seen as scary has now become commonplace. They understand that a person who has a tattoo does not mean someone who is not intellectual or has no skills. They are free people and appreciate the art that is applied to their bodies. As long as its existence does not disturb others there should be no problems and there is no need to label the tattooed person as evil or close to deviant behavior.Keywords: Mentawai Tattoos, Tattoo Perception,